SYNTHESIS AND STUDY OF ANTIOXIDANT ACTIVITY OF [(1-ARYL-5-FORMYL-1H-IMIDAZOLE-4-IL)THIO]PROPIONIC ACIDS - A. O. Palamar; A. M. Grozav; V. O. Chornous; I. M. Yaremiy; M. V. Vovk (Zaporozhye State Medical University, 2014)
Introduction. Derivatives of imidazole belong to the promising group of compounds for antioxidant activity study, due to the series of recent publications. This is defined by special features of their structure, specific reactivity and significant potential of pharmacological action. Earlier during process of looking for new antioxidants we studied significant amount of imidazole derivatives, among which the [(1-aryl-5-formylimidazole-4-il)thio]acetic acids structurally modified by the formyl group and thioacetic acid fragment, are especially worth noting. The purpose of the study. Synthesis of [(1-aryl-5-formylimidazole-4-il)thio]propionic acids and comparison of their antioxidant effect with [(1-aryl-5-formylimidazole-4-il)thio]acetic acids with to identify prospects of in-depth study of the most active compounds as antioxidants. Materials and methods. The method based on interaction of available 4-chloro-5-formylimidazoles with thiopropionic acid was proposed for the synthesis of [(1-aryl-5-formylimidazole-4-il)thio]propionic acids. The reaction takes place in ethanol in presence of potassium hydroxide and leads to the target compounds with yields of 81-86%. The study of antioxidant activity of synthesized compounds was conducted in vitro by speed inhibition value of rats' liver endogenous lipids ascorbate-dependent peroxide oxidation. It was determined by concentration of one of the final products of free radical oxidation of lipids (FROL) - maleic aldehyde (MA) in the investigated sample. Concentrations of synthesized compounds were chosen within concentrations which were studied for thiotriazolin (manufactured by corporation "Arterium", Ukraine, solution for injection, 25 mg/ml). The results of the study and their discussion. Preparative method for the synthesis of [(1-aryl-5-formylimidazole-4-il)thio]propionic acids has been designed. Imidazolylthiopropionic acids have been synthesized; they are crystalline compounds, of light-yellow color, well soluble in solutions of alkali and in organic solvents. Their composition and structure has been reliably confirmed by elemental analysis and by results of IR-, 1H, 13C NMR and chromatography mass-spectra measurements. The results of in vitro antioxidant activity screening of synthesized compounds show pronounced antioxidant effect of all of the studied compounds. It has been determined that the thiopropionic acid's derivatives show much higher in vitro activity than the derivatives of the thioacetic acid. The maximum inhibition level of Fe2+-ascorbate initiated FROL in the rats' liver in vitro under the action of these compounds varies in the range between 67-72% in comparison with the control samples. The produced results indicate that with the growth of the carbon chain length of the thioalkanecarboxylic acids' fragment the antioxidant activity of the studied compounds grows. Conclusions. 1. By interaction of 4-chloro-5-formylimidazoles with thiopropionic acid in the presence of potassium hydroxide the new [(1-aryl-4-chloro-1H-imidazole-5-il)methyl]thiopropionic acids have been synthesized with high yields. 2. All studied derivatives of imidazole in the range of concentrations of 10-3-10-1М show high antioxidant activity in the in vitro system. 3. The comparison of antioxidant activity of [(1-aryl-5-formylimidazole-4-il)thio]acetic and propionic acids has shown that the increasing of methylene groups' quantity in the carboxyalkylthiol fragment leads to increasing of the antioxidant effect of the synthesized compounds.